Temporal effects on spectroscopic line shapes, resolution, and sensitivity of the broad-band sum frequency generation - Stiopkin, Igor V.; Jayathilake, Himali D.; Weeraman, Champika; Benderskii, Alexander V. (The Journal of chemical physics, 2010)
Sum frequency generation (SFG) is a surface-selective spectroscopy that provides a wealth of molecular-level information on the structure and dynamics at surfaces and interfaces. This paper addresses the general issue of spectral resolution and sensitivity of the broad-band (BB) SFG that involves a spectrally narrow nonresonant (usually visible) and a BB resonant (usually infrared) laser pulses. We examine how the spectral width and temporal shape of the two pulses, and the time delay between them, relate to the spectroscopic line shape and signal level in the BB-SFG measurement. By combining experimental and model calculations, we show that the best spectral resolution and highest signal level are simultaneously achieved when the nonresonant narrow-band upconversion pulse arrives with a nonzero time delay after the resonant BB pulse. The nonzero time delay partially avoids the linear trade-off of improving spectral resolution at the expense of decreasing signal intensity, which is common in BB-SFG schemes utilizing spectral filtering to produce narrow-band visible pulses.